(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, the experiments will be conducted to improve the surface finish quality of aluminum alloy 6061 work piece by using carbide tips. The type is bull nose tip. A series of experiments will be done by varying the milling parameters spindle speed, feed rate and depth of cut. The spindle speeds are 3500rpm, 3000rpm and 2000rpm. The feed rates are 200mm/min, 300mm/min and 400mm/min. Depth of cut is 0.2mm and 0.3mm and 0.4mm. Taguchi method is used to study the effect of process parameters and establish correlation among the cutting speed, feed and depth of cut with respect to the major machinability factor, surface finish. Validations of the modeled equations are proved to be well within the agreement with the experimental data. Taguchi method is used to study the effect of process parameters and establish correlation among the cutting speed, feed and depth of cut with respect to the major mach inability factor, surface finish. Validations of the modeled equations are proved to be well within the agreement with the experimental data.